Lack of IL7Rα expression in T cells is a hallmark of T-cell immunodeficiency in Schimke immuno-osseous dysplasia (SIOD) - Sanyal, Mrinmoy (Clinical immunology (Orlando, Fla.), 2015)
Copyright © 2015 Elsevier Inc. All rights reserved.